IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS KAHOOT PADA MATA PELAJARAN IPS DI MTS MA’ARIF NU KOTA MALANG - Azizah, Siti Nur (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2025)
As technology in education continues to develop, teachers are required to be more creative in designing learning methods. Based on observations at MTs Ma’arif NU Kota Malang, it was found that Social Studies learning—particularly in history material—is often considered boring, with too many reading materials that make students reluctant to read. In response to this issue, the Social Studies teacher at MTs Ma’arif NU Kota Malang implemented game-based learning using Kahoot. The research problem in this study is how the implementation of Kahoot-based media in Social Studies learning at MTs Ma’arif NU Kota Malang is carried out, as well as the supporting and inhibiting factors. The approach used is a qualitative approach with a descriptive type, utilizing interview, observation, and documentation techniques. The results of the study show that the implementation of Kahoot-based media in Social Studies learning at MTs Ma’arif NU Kota Malang consists of three stages: planning, implementation, and evaluation. The supporting factors in using Kahoot include the availability of facilities and infrastructure, support from the school, the teacher’s skills, and students’ enthusiasm. On the other hand, the inhibiting factors include technical issues, limited time, dense material, and lack of student preparation. Despite these supporting and inhibiting factors, the researcher found that learning media using Kahoot is suitable for classroom application and can serve as an alternative for teachers to diversify learning models.